Diagnosis and Management of Klatskin Tumor - Dicky Levenus Tahapary; Rudy Hidayat; Achmad Fauzi; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2010)
Klatskin tumor is a cholangiocarcinoma in bifurcatio areas and related to poor prognosis. Surgery is the only curative method, but endoscopy also has a role in diagnostic as well as therapeutic measures. This report shall discuss a case of Klatskin tumor in which to establish diagnosis, multimodal imaging using ultrasonography, computed tomography, endoscopic retrograde cholangiopancreatography (ERCP), and tumor markers were used. For palliative therapeutic measures in this case, placement of plastic stents by ERCP was performed. The procedure ERCP with stents placement can be an option in the management of Klatskin tumor, in which surgery is not possible to be conducted. Keywords: Klatskin tumor, ERCP, stent, diagnosis, management